Keanekaragaman Dan Kelimpahan Serangga Polinator Pada Perkebunan Mentimun (Cucumis sativus L) Desa Waiheru Ambon - Allifah AF, Asyik Nur; Bahalwan, Farida; Natsir, Nur Alim (Biosel Biology Science and Education, 2020)
Pollinator insects are insects that play a role in pollination, namely intermediaries pollinating plants. The purpose of this study was to determine the abundance and diversity of insects pollinators in the Cucumber (Cucumis sativus L) Plantation of Waiheru Village, Baguala District, Ambon City. Sampling was done by purposive sampling using a yellow glue trap (Yellow sticky trap). The customer observations are made in visual control. Observation starts at 07.00 WIT until 18.00 WIT which is divided into 3 time periods, namely: 07.00-10.00 WIT, 11.00-14.00 WIT and 15.00-18.00 WIT. The data obtained were analyzed using the diversity index (H ') according to Shannon and Wiener. The results showed that the total abundance of pollinator insects in vegetable plantations was 1220 individuals, consisting of 3 orders and 5 families. Insect families that play a role in the process of pollination are Family Apidae, Formicidae, Syrpidae, Muscidae and Papilionidae. The highest abundance of insects is dominated by the Formicidae Family while the lowest abundance is the Papilionidae Family. Value insect pollinator diversity found among the sites that H '= 1.21 which indicates that the level of diversity of insect pollinators on plantations Cucumber (Cucumis sativus L) in the Waiheru Village, Baguala District, Ambon City in the medium category.